In vitro inhibition of shikimate hydroxycinnamoyltransferase by acibenzolar acid, the first metabolite of the plant defence inducer acibenzolar-S-methyl - Negrel, Jonathan (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.